2015
DOI: 10.1108/ajim-10-2014-0134
|View full text |Cite
|
Sign up to set email alerts
|

Authors self-citation behaviour in the field of Library and Information Science

Abstract: Purpose – The purpose of this paper is to analyse the author self-citation behavior in the field of Library and Information Science. Various factors governing the author self-citation behavior have also been studied. Design/methodology/approach – The 2012 edition of Social Science Citation Index was consulted for the selection of LIS journals. Under the subject heading “Information Science and Library Science” there were 84 journals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
11
0
2
Order By: Relevance
“…For macro level studies, Glanzel and Thijs (2004) reported that multi-authorship does not exaggerate the extent of self-citations. In the field of Library and Information Science, although Dimitroff and Arlistsch (1995) observed a positive relation between the number of self-citations and number of co-authors, Shah, Gul and Gaur (2015) could not ascertain such relationship. However, irrespective of the number of co-authors, Shah, Gul and Gaur (2015) found that collaborative works attract more citations than works produced at individual level.…”
Section: Literature Reviewmentioning
confidence: 75%
See 3 more Smart Citations
“…For macro level studies, Glanzel and Thijs (2004) reported that multi-authorship does not exaggerate the extent of self-citations. In the field of Library and Information Science, although Dimitroff and Arlistsch (1995) observed a positive relation between the number of self-citations and number of co-authors, Shah, Gul and Gaur (2015) could not ascertain such relationship. However, irrespective of the number of co-authors, Shah, Gul and Gaur (2015) found that collaborative works attract more citations than works produced at individual level.…”
Section: Literature Reviewmentioning
confidence: 75%
“…It may be noted that where excessive self-citations are regarded as an abuse (Lawani 1982;Martyn 1975), their prevalence in fair number is perceived as normal (Aksnes 2003) and even commendable, if only to avoid the repetition of already published information (Macdonald and Kam 2011). Authors have mostly studied self-citations in specific subject fields, such as Plant Physiology and Neurobiology (Tagliacozzo 1977); Library and Information Science (Dimitroff and Arlitsch 1995;Shah, Gul and Gaur 2015); Ecology (Pichappan and Sarasvady 2002); Diabetes Mellitus (Gami et al 2004); General Medicine (Kulkarni et al 2011); Otolaryngology (Tolisano, Song and Cable 2015), and have mostly examined self-citations with regard to their frequency in an article (the number of times they occur in an article).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-citation is a common phenomenon in the process of disseminating scientific knowledge (Glänzel et al, 2006;Shah et al, 2015). In Library and Information Science, several papers offer evidence that about half the papers published in specialized journals contain at least one instance of self-citation (Dimitroff and Arlitsch, 1995;Davarpanah and Aslekia, 2008).…”
Section: Control Indicatorsmentioning
confidence: 99%